Chemical Pulps for Writing and Printing Papers from Cymbopogon citratus (DC.) Stapf (West Indian Lemon Grass) - Guha, S. R. D.; Pant, Rajesh; Karira, B. G. (Indian Forester, 1973)
Laboratory experiments on the production of chemical pulps for writing and printing papers by soda process from Cymbopogon citratus (DC.) Stapf after extracting the essential oil are described. The average fibre length Was 0.94 mm and the average fibre diameter was 0.013 mm. Bleached pulps, only in lower yields and less strength properties than sabal grass could be prepared from this raw material.